Clinical and microbiological features of Haemophilus influenzae vulvovaginitis in young girls. Issue 12 (1st December 2002) - Cox, R A; Slack, M P E
Abstract : Aims: To define the clinical and microbiological features of vulvovaginitis in prepubertal girls whose genital swabs yielded Haemophilus influenzae . Methods: Laboratory based study and retrospective collection of clinical data from the requesting doctors. Results: Thirty eight isolates of non-capsulate Haemophilus influenzae and one of H parainfluenzae were isolated from 32 girls aged 18 months to 11 years. No other pathogens, such as β haemolytic streptococci or yeasts, were present with H influenzae. The most common biotype was biotype II, comprising 57% of the 26 isolates biotyped. Six children had more than one episode of vulvovaginitis caused by H influenzae and a total of 14 children had recurrent vaginal symptoms. Conclusion: Children who have H influenzae vulvovaginitis are at risk of recurrent symptoms. Biotype II is the one most commonly associated with this condition.